Development Hypothetical Learning Trajectory on Statistics Material in Grade VIII Using Realistic Mathematics Education at the Preliminary Stage with Pranata Mangsa Context - Nursyahidah, Farida; Albab, Irkham Ulil; Rubowo, Maya Rini; Tuni’mah, Lattifah; Febriansyah, Muhammad Aldo; Hardiyanto, Dwi; Atmaja, Satriya Adika Arif (Jurnal Pendidikan Matematika, 2024)
Statistics is a staple in the curriculum because it is considered necessary in everyday life. However, students often find statistics challenging. Students' difficulties in learning statistics are caused by several factors, including a lack of understanding of mathematical concepts and principles in solving problems. This study aimed to design and develop a Hypothetical Learning Trajectory (HLT) for grade VIII statistics using the Realistic Mathematics Education (RME) approach, with Pranata Mangsa as the learning context. The method used in this research was validation-type design research. This research produced an HLT of statistics material using pranata mangsa context consisting of 3 activities to help students understand and master the material. The activities of the HLT are 1) collecting, presenting, and analyzing data, 2) measuring centralized data, and 3) measuring data distribution. The results showed an HLT for teaching statistics using RME that can effectively support students of all ability levels. This HLT allows students to rediscover statistics concepts through horizontal and vertical mathematical processes. Finally, the HLT facilitates students to create their models from informal to formal and increases the interaction between students and teachers. Statistika menjadi materi pokok dalam kurikulum karena dianggap penting dalam kehidupan sehari-hari. Namun, pada kenyataannya statistika merupakan salah satu pelajaran yang dianggap sulit bagi siswa. Kesulitan siswa dalam belajar statistika disebabkan oleh beberapa faktor, diantaranya kurangnya pemahaman konsep dan prinsip-prinsip matematika dalam menyelesaikan soal. Tujuan penelitian untuk mendesain dan mengembangkan Hypothetical Learning Trajectory (HLT) menggunakan pendekatan Realistic Mathematics Education (RME) pada materi statistika kelas VIII menggunakan konteks Pranata Mangsa yang menjadi starting point dalam pembelajaran. Metode yang digunakan dalam penelitian ini adalah design research tipe validasi. Penelitian ini menghasilkan HLT materi statistika menggunakan konteks pranata mangsa yang terdiri dari 3 iceberg untuk membantu siswa dalam memahami dan menguasai materi. Adapun iceberg dari HLT tersebut adalah 1) mengumpulkan, menyajikan, dan menganalisi data; 2) ukuran pemusatan data; dan 3) ukuran penyebaran data. Hasil penelitian ini menunjukkan bahwa HLT mampu membantu siswa menemukan kembali konsep statistika melalui proses matematika horizontal dan vertikal. HLT memfasilitasi siswa untuk membuat model mereka sendiri dari informal ke formal dan meningkatkan interaksi antara siswa dan guru.